2017
DOI: 10.2131/jts.42.683
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cytotoxicity caused by forming a complex of copper and 2,9-dimethyl-1,10-phenanthroline in cultured vascular endothelial cells

Abstract: -Organic-inorganic hybrid molecules, which are composed of organic-ligand(s) and metal(s), are indispensable as synthetic reagents in chemistry, but they have made very little in the way of contributions to biological research. Previously, we reported that the cytotoxicity of organic-inorganic hybrid molecules in vascular endothelial cells depends on interactions between the intramolecular metal and ligand, but remains independent of the hydrophobicity of the intramolecular metal(s). Herein, we show a synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…3B). Thus, it is suggested that DMP, which is the ligand structure of Zn-DMP, is responsible for the modulation of proteoglycan had been reported previously (Nakamura et al, 2017). These results suggest that there are metals that partly disturb the modulation of endothelial proteoglycan synthesis by DMP, regardless of cell density.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…3B). Thus, it is suggested that DMP, which is the ligand structure of Zn-DMP, is responsible for the modulation of proteoglycan had been reported previously (Nakamura et al, 2017). These results suggest that there are metals that partly disturb the modulation of endothelial proteoglycan synthesis by DMP, regardless of cell density.…”
Section: Discussionsupporting
confidence: 62%
“…2,9-dimethyl-1,10-phenanthroline (DMP) was obtained from Tokyo Chemical Industry (Tokyo, Japan) and DMP complexes (shown in Fig. 1) were synthesized, as previously described (Nakamura et al, 2017). The QIAzol lysis reagent was purchased from QIAGEN (Valencia, CA, USA), and GeneAce SYBR qPCR mix α was obtained from Nippon Gene (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, organic-inorganic hybrid molecules, including zinc complexes, can exhibit distinct biological activities from that of the intramolecular metal in inorganic forms (Fujie et al, 2016a). The biological activities, including cytotoxicity, of either the molecular structures or that of the metals that make up the hybrid molecules cannot be used to predict the biological activities of such hybrid molecules (Kohri et al, 2015;Murakami et al, 2015;Hara et al, 2016;Nakamura et al, 2017). The present study demonstrated that Zn-06 could significantly accumulate within various cell types and exhibited cytotoxicity in cells..…”
Section: Discussionmentioning
confidence: 74%
“…endothelial cells. On the other hand, the strategy showed that cytotoxicity of organic-inorganic hybrid molecules is different from that of either intramolecular metal in an inorganic form or the ligand (Kohri et al, 2015;Nakamura et al, 2017;Hara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the importance of toxicology in organic-inorganic hybrid molecules is increasing (Fujie et al, 2016b). Previously, we have shown the toxicological results of trivalent organoantimony compounds; the cytotoxicity and intracellular accumulation of these molecules can be changed by the intramolecular metal element and organic structure (Kohri et al, 2015;Hara et al, 2018b;Nakamura et al, 2017). As antimony is an element that can take not only a trivalent but also pentavalent form, we investigated the relationships among the hydrophobicity, intracellular accumulation, and cytotoxicity of pentavalent organoantimony compounds with three phenyl groups in cultured vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%